Factors Affecting Employee Performance: A Study of Employees at the Semarang Container Terminal - Hanif Nashiruddin Mufid; Artha Febriana; Sih Darmi Astuti; Mila Sartika (Journal Research of Social Science, Economics, and Management, 2026)
Background: The phenomenon of increasing awareness of work–life balance as a result of the COVID-19 pandemic underlies this research. Objective: This study aims to analyze the influence of Work-Life Balance, Work Environment, and Workload on the performance of employees at Semarang Container Terminal. Methods: This study employs a quantitative approach by distributing questionnaires to 90 respondents who work at the Semarang Container Terminal, selected through purposive sampling. The collected data were analyzed using the SPSS data processing application. Results: The results indicate that work–life balance, work environment, and workload have a significant effect on employee performance, both simultaneously and partially. Conclusion: These findings suggest that companies should consistently maintain employees’ work–life balance, provide a supportive work environment, and ensure a proportional workload to sustain employee productivity and optimize overall employee performance.The practical implications of this study confirm that employee welfare programs that cover these three aspects are a strategic investment for the company, as they are proven to be able to significantly improve performance, as well as the basis for management to evaluate human resource policies to be more oriented towards the holistic well-being of employees.